Innovative Printmaking : The Making of two- and three-dimensional Prints and Multiples - Newman, Thelma R. (New York : Crown Publishers Inc., 1977)
Albers, Jospeh ; Allen, Jessie ; Appel, Karel ; Burke, Gay ; Burg, Patricia Jean ; Callot, Jacques ; Falkenstein, Claire ; Fragonard, Jean Honoré ; Gates, Jeff ; Hackman, Vida ; Hanson, Jo ; etc.
Engels
boek